Masa Enam Bulan Berpisah Tempat Tinggal Sebagai Syarat Formil Pengajuan Perceraian dengan Alasan Pertengkaran: Studi Putusan Mahkamah Agung No 421 K/Ag/2023) - Hanafi Ilba; Ibnu Radwan Siddik Turnip (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
From a jurisprudence perspective, there is no requirement for a long period of separation between husband and wife to carry out a divorce for reasons of quarrels and disputes. This research aims to analyze the six month period of separation of residence between husband and wife as a formal requirement in filing for divorce on the grounds of quarrels and disputes as stated in the consideration of Supreme Court Decision No. 421 K/AG/2023. What is the real reason and aim of the judge in requiring the 6 month period, so that the Supreme Court's decision has canceled the decision of PA Tegal No. 312/Pdt.G/2022/PA.Tg and PTA Semarang decision no. 334/Pdt.G/2022/PTA. SMg. This research is normative legal research, using secondary data sourced from primary legal materials and secondary legal materials. Primary legal material was obtained from the Supreme Court Decision, PTA Semarang and PA Tegal Decisions, while secondary legal material was obtained from fiqh books and Supreme Court Circulars. The results of the research show that the judge's reasons for requiring a six-month period of separation between husband and wife as a formal condition for filing a divorce due to arguments are based on the new provisions contained in SEMA No. 1 of 2022 which confirms that divorce cases are based on ongoing disputes and quarrels. can be granted if it is proven that the husband/wife has had continuous disputes and quarrels or separated residences for at least 6 (six) months. This judge's decision is considered aimed at increasing family resilience and making it more difficult for divorce to occur in society, which is part of the principles of marriage.